HOW TO KEEP LOYAL RELATIONSHIPS WITH SERVICE CUSTOMERS USING HOLISTIC MARKETING - B. E. HAJIKULOV (International Journal of Innovations in Engineering Research and Technology, 2021)
In today’s economic uncertainty and turbulence, creating and maintaining loyal relationships with service customers over the long term represents a necessary condition for business success. Winning in times like these requires recognizing the key role that customers and their experiences play in overcoming challenging economic circumstances. In this paper we present effective techniques to achieving customer loyalty; and also holistic marketing as a successful strategy for reaching the same goal.